Validation of clinical techniques for verification of uniform attenuation earplugs. (25th January 2019) - Portnuff, Cory D. F.; Price, Drew
Abstract: Objective: Uniform attenuation earplugs (UAE) theoretically provide near even attenuation across frequencies when built to a manufacturer's specifications. Unfortunately, there is no current research available confirming if custom-molded uniform attenuation earplugs (UAE) are made to specifications nor is there guidance available on clinical methods of measuring attenuation of uniform attenuation earplug (UAE) devices. The goal of this study was to evaluate different procedures for UAE verification and to determine the most accurate clinically accessible verification protocol. Design: Attenuation was measured using probe microphone techniques, as well as real-ear attenuation at threshold (REAT) measurements under circumaural earphones, soundfield speakers and supra-aural earphones. Comparisons were made to a reference system created in the laboratory. Study sample: Seventeen adult participants, totaling 30 ears. Results: The results of this study demonstrate that the REAT measured in the soundfield using a narrowband noise stimulus with masking in the contralateral ear is currently the most accurate and widely available method of verifying UAEs. Conclusions: Factoring in clinical efficiency, the authors of this study recommend verifying attenuation levels using a soundfield REAT procedure as best clinical practice. In addition, the data suggests that REAT measurements under circumaural earphones are an acceptable second choice method.